Drilling into mines for heat: geological synthesis of the UK Geoenergy Observatory in Glasgow and implications for mine water heat resources. Issue 1 (2022) - Monaghan, Alison A.; Starcher, V.; Barron, H. F.; Shorter, K.; Walker-Verkuil, K.; Elsome, J.; Kearsey, T.; Arkley, S.; Hannis, S.; Callaghan, E.
No abstract available